Short term versus conventional Catheterisation after Genital Prolapse Surgery (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
This Randomised controlled clinical trial was undertaken to determine the suitable time of catheter removal after urogenital prolapse surgery in order to reduce the catheter related UTI and its long term sequel. Method: Total 80 patients undergoing vaginal hysterectomy with pelvic floor repair were enrolled and randomised into two equal groups by lottery method. Trans-urethral catheter was removed on 2nd & 5th post operative day in group I (n=40) and in group II (n=40) respectively. Post   voidal residual urine volume before operation and after removal of catheter was measured in   all patients by ultrasound scanning. Re-catheterisation was done for three more days if residual volume > 200ml after removal of catheter. Urine samples were taken before removal of catheter and send for routine microscopic examination and culture & sensitivity test to detect UTI.Results: Removal of catheter on 2nd post-operative day lead to significant reduction of rate of UTI. The rate of UTI following removal of catheter was 7.5% versus 42.5% in group I and in group II (p